AN ERROR ANALYSIS OF SIMPLE PRESENT IN WRITING DESCRIPTIVE TEXT THROUGH THE ELEVENTH GRADE STUDENTS: Analisis Kesalahan Simple Present Dalam Menulis Teks Deskriptif Pada Siswa Kelas Sebelas - Nurwanti, Nurwanti (Uniqbu Journal of Social Sciences, 2021)
The research was conducted to identify the errors are made by the eleventh grade of IPA students at Madrasah Aliyah Al Ikhlas Amberi in writing descriptive text by using simple present. The objective of the research is to find out the type of errors made in writing descriptive text by using simple present. This research applied descriptive qualitative research method by using Surface Strategy Taxonomy to analyze the data. The result of this research showed that the total of errors were 279 errors. The proportions (frequency and percentage) of the students’ error in writing descriptive text by using simple present was, students made errors in omission type were 27 students with 74 errors or 26,52% of errors, students made errors in addition type were 19 students with 37 errors or 13,26 % of errors, students made errors misformation type were 30 students with 142 errors or 51,00 % of errors, and students made errors in misordering type were17 students with 26 errors or 9,31 % of errors. From the data above, it could be concluded that misformation type was the highest number of errors made by the students and misordering type was the lowest number of errors made by the students.